(untitled) (Research, Society and Development, 2022)
The objective of the research was to evaluate the distribution of stress produced by surgically assisted rapid maxillary expansion in the maxillary structures using the bone-supported expander device by the Finite Element Method. Material and methods: A three- dimensional model was simulated for surgery with a LeFort I osteotomy with pterygomaxillary disjunction using a bone-supported device model for the 1mm aperture. The results showed a greater opening of the maxilla in the anterior region and a smaller opening in the posterior region. The tension forces showed mainly in all the palatine face and the posterior alveolar bone and tuber, as well as in the epilating zygomatic region above the osteotomy. The stress showed little dissipation for the roots of the molar. The forces of compression were manifested in the pterygoid process and the zygomatic pillar adjacent to the osteotomies, as well as in the expander areas of contact with the palatine bone. The analysis showed that the most stressed part is the rod connecting the device module to the support platform. Conclusion: The resulting tension stresses transmitted to the alveolar bone of the teeth adjacent to the appliance did not seem to be sufficient to displace the teeth.